Self-Regulation Approach to Training Child and Family Practitioners. - Mazzucchelli, Trevor; Ralph, A. (Springer, 2019)
Evidence-based psychotherapies or programs (EBPs) exist for most mental health disorders that occur in childhood; however, the majority of children with a mental health disorder do not receive such treatments. This research-practice gap has been attributed to a range of factors that complicate the delivery of EBPs in everyday practice. While most suggestions to bridge this gap have focused on how to develop EBPs that will have a better fit for the clinical settings in which they will ultimately be deployed, a useful adjunct is to enhance practitioners' capacity to flexibly deliver EBPs to manage these factors. We propose that the extent to which a practitioner is able to change their own behaviour in response to cues and information about the current needs of their clients, and do so while maintaining the integrity of an EBP, may be a function of practitioners' self-regulatory capacity. In this conceptual paper, we describe a model of self-regulation that can be applied to child and family practitioners. We argue that practitioners with greater self-regulatory capacity are more likely to take up EBPs, sustain their use of them and have superior outcomes with clients. We draw on our experience in disseminating a system of parenting support to illustrate how practitioners' self-regulatory capacity can be enhanced while simultaneously receiving training in an EBP. Advantages and disadvantages of a self-regulatory approach to training are discussed and directions for future research are offered.